Elbow dysplasia in a Basset Hound - Kapatkin, A. S.; Volk, S. W.; Keith, D. G.; McLear, R. C.; Smith, G. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
A Basset Hound with elbow dysplasias (ununited anconeal process and elbow incongruity in the left elbow, fragmented medial coronoid process and elbow incongruity in the right elbow) was followed by serial radiography, computer tomographic (CT) scan and arthroscopy at eight,11,13,16 and 19 months of age. Radiographs were insensitive to progressive changes in the elbow dysplastic joints. CT and arthroscopy were both highly sensitive to subtle and severe changes occurring in the elbow joint over the times examined. Further studies evaluating the effect of multiple arthroscopic examinations itself on joints as well as age that CT will be sensitive to the earliest changes in the elbow joint need to be investigated. Hopefully, these studies will help evaluate early surgical interventions and help to eliminate elbow dysplasia in breeding dogs.
Keywords: Elbow dysplasia; elbow computed tomography; elbow arthroscopy